2008
DOI: 10.1007/s00464-008-9962-4
|View full text |Cite
|
Sign up to set email alerts
|

Complications with laparoscopically assisted gastrectomy: multivariate analysis of 300 consecutive cases

Abstract: Background Complications associated with laparoscopically assisted gastrectomy (LAG) are not significantly different from those associated with open gastrectomy. However, additional risks related to abdominal access, pneumoperitoneum, and special electrosurgical instruments result in an increased incidence of complications with LAG. This study analyzed the causes and risk factors linked to postoperative morbidity. Methods A retrospective review analyzed the data of 300 patients who underwent consecutive LAG fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 23 publications
3
42
1
1
Order By: Relevance
“…Adjusted OR time for LTG was approximately 60 min longer, which seemed to partially correspond with other combined studies that reported LTG being 20–60 min longer than LPG [18,19,20]. These studies evaluated data from a single high-volume center, while the findings of our study were from community-based centers and the variation of OR time between LPG and LTG was reasonable.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Adjusted OR time for LTG was approximately 60 min longer, which seemed to partially correspond with other combined studies that reported LTG being 20–60 min longer than LPG [18,19,20]. These studies evaluated data from a single high-volume center, while the findings of our study were from community-based centers and the variation of OR time between LPG and LTG was reasonable.…”
Section: Discussioncontrasting
confidence: 44%
“…However, complications were restricted to surgical or procedure-related, but not medical, complications [18,19]. Hospital teaching status explained the variation of complications, while hospital volume was not associated with complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, we noted that it is very difficult to perform a gastrojejunostomy via a minilaparotomy in severely obese patients with a thick abdominal wall, even if the small incision is extended. Park et al [22] reported that 7 % (21/ 300) of patients experienced postoperative wound infection after LADG. In R-Y reconstruction after TLDG, the gastrojejunostomy is performed intracorporeally.…”
Section: Discussionmentioning
confidence: 99%
“…Domestic and international multicenter, prospective, randomized, controlled clinical trials of the application of laparoscopic surgery to early gastric cancer treatment have shown the short-term efficacy of laparoscopic gastrectomy to be better than that of conventional laparotomy, while the long-term efficacy is equivalent [10]. Laparoscopic D2 radical gastrectomy has been confirmed to be technically safe and feasible for the treatment of progressive gastric cancer, and this technique has achieved good short-term efficacy [11,12]. Application of laparoscopy in gastric cancer surgery has been gradually developed domestically and internationally.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first report of laparoscopic radical gastrectomy by Kitano et al [1] from Japan in 1994, this technique has resulted in impressive treatment outcomes [2,3,4] due to its significant advantage of minimal invasion as opposed to the traditional radical gastrectomy. However, in cases of progressive gastric cancer, particularly those with serosal invasion, it remains unclear whether CO 2 pneumoperitoneum affects peritoneal metastasis of gastric cancer after surgery.…”
Section: Introductionmentioning
confidence: 99%